"Education just a game when you can play Indians [sic] or Eskimos [sic] with Museum exhibits" (Philadelphia Evening Bulletin, 1942)
Helen Ehrline, Lloyd Erdman and Charlie Fisher play African instruments at the University of Pennsylvania Museum of Archaeology and Anthropology. Title from clipping caption